Multimodality and listening comprehension: Testing and implementing classroom material - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2018)
Author/s Elena Domínguez Romero Carmen Maíz Arévalo Universidad Complutense de Madrid, Spain   ABSTRACT In recent decades, multimodality has gained an increasing amount of attention. Accordingly, multimodal analysis has eventually widened its research into the realm of language teaching and learning in what is currently known as Applied Multimodality. The present article intends to make a contribution to this field by focusing on the role played by multimodality in listening comprehension, taking into account three main aspects: the arrangement of information value, salience and framing. In order to show the extent to which multimodality can affect our students' comprehension, we provided a group of First Certificate university students with two versions of ten listening tasks. After analysing them, these original listening activities were processed using Photoshop so as to either improve or impoverish their multimodal input and students were required to work on one of the two versions. Results prove that, in general, multimodality has a say in hindering or helping listening comprehension.